Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 107279 by mathdave last updated on 09/Aug/20

Commented by Dwaipayan Shikari last updated on 10/Aug/20

As x→0  tanx→x  lim_(x→0) ((x^x^x^x^x^x^      /x^x^x^x^x^x^(??)      ))=1

Asx0tanxxlimx0(xxxxxxxxxxxx??)=1

Answered by 1549442205PVT last updated on 10/Aug/20

We insert the symbol for convenient  I_n =lim_(n→∞) (lim_(x→0) ((((tanx)^( (tanx)^(  (tanx)...) ) ^(↽^(n times) ) )/x^x^(x...)  _⌣_(n times)  )))  =lim_(x→0) ((f_n (x))/(g_n (x)))  =where f_k (x)=(tanx)^( (tanx)^(   (tan x)...) )  ^(↽^(k times) )   g_k (x)=x^x^(x....)    ^(↽^(k times) )   We prove that I_n =1 for ∀n∈N,n≥1  Indeed,for n=1 we have  I_1 =lim_(x→0) ((tanx)/x)=lim_(x→0) ((sinx)/x).(1/(cosx))=1.(1/1)=1  I_2 =lim_(x→0) ((tanx^(tanx) )/x^x )⇒lnI_2 =lim_(x→0) (ln((tanx^(tanx) )/x^x ))  =lim_(x→0) (tanxln(tanx)−xln(x))  We have lim_(x→0) (tanxln(tanx))=  J=lim_(x→0) ((lntanx)/(1/(tanx))).This is the form (∞/∞).Hence  apply L′Hopital we get  J=(((1+tan^2 x)/(tanx))/(−(1/(tan^2 x))(1+tan^2 x)))=lim_(x→0) (−tanx)=0  K=lim_(x→0) (xlnx)=lim_(x→0) (((lnx)/(1/x)))=lim_(x→0) ((1/x)/((−1)/x^2 ))  =lim_(x→0) (−x)=0  Thus,lnI_2 =0⇒I_2 =e^0 =1.We see that  the assertion is true for n=1,2.Now  suppose that assertion was true for  ∀n=1,2,....,k.We need to prove that  it is also for n=k+1.Indeed,we  conside I_(k+1) =(lim_(x→0) ((((tanx)^( (tanx)^(  (tanx)...) ) ^(↽^((k+1) times) ) )/x^x^(x...)  _⌣_((k+1) times)  )))  Then  lnI_(k+1) =lim(((tanxlnf_k (x))/(xlng_k (x))))  ⇒lnI_(k+1) =lim_(x→0) [ln(f_k (x)^(tanx) )−ln(g_k (x)^x ]  +for k=1 by above proof was true   +Suppose it is true ∀n=1,2,...,k  which means I_k = lim_(x→0) ( ln((f_k (x))/(g_k (x))))=0 ∀k=1,2,...,k  Then lnI_(k+1) =lim[ln(((f_k (x)^(tanx) )/(g_k (x)^x )))]  =lim[tanxln(f_k (x))−xln(g_k (x))]  =lim_(x→0) {tanx[ln(f_k (x))−ln(g_k (x))]+  tanxln(g_k (x))}=0 since   [ln(f_k (x))−ln(g_k (x))]=0 by  introduction the hypothesis and   ln(xg_k (x))→0 when x→0.Indeed,this can   is prove by induction follows as:  +for k=1 we have lim_(x→0)  [xlng_1 (x)]=  =lim_(x→0) (xlnx)=lim_(x→0) ((lnx)/(1/x))=lim_(x→0) ((1/x)/((−1)/x^2 ))=lim_(x→0) (−x)=0  +Suppose it is true ∀n=1,2,...,k  +Then lim_(x→0) [ln(g_(k+1) (x))]=lim[_(x→0) xln(g_k (x))]  =0.0 due to lim[ln(g_k (x))]=0 (by   introduction the hypothesis).This  show that lim_(x→0) [xln(g_k (x))]=0 true ∀n≥1  Thus ,we  prove that ln I_(k+1) =0 is true  ,so by introduction primciple lnI_n =0  is true ∀n≥1.⇒I_n =e^0 =1∀n∈N,n≥1  (q.e.d)

WeinsertthesymbolforconvenientIn=limn(limx0((tanx)(tanx)(tanx)...ntimesxntimesxx...))=limx0fn(x)gn(x)=wherefk(x)=(tanx)(tanx)(tanx)...ktimesgk(x)=xxx....ktimesWeprovethatIn=1fornN,n1Indeed,forn=1wehaveI1=limx0tanxx=limx0sinxx.1cosx=1.11=1I2=limx0tanxtanxxxlnI2=limx0(lntanxtanxxx)=limx0(tanxln(tanx)xln(x))Wehavelimx0(tanxln(tanx))=J=limx0lntanx1tanx.Thisistheform.HenceapplyLHopitalwegetJ=1+tan2xtanx1tan2x(1+tan2x)=limx0(tanx)=0K=limx0(xlnx)=limx0(lnx1x)=limx01x1x2=limx0(x)=0Thus,lnI2=0I2=e0=1.Weseethattheassertionistrueforn=1,2.Nowsupposethatassertionwastrueforn=1,2,....,k.Weneedtoprovethatitisalsoforn=k+1.Indeed,weconsideIk+1=(limx0((tanx)(tanx)(tanx)...(k+1)timesx(k+1)timesxx...))ThenlnIk+1=lim(tanxlnfk(x)xlngk(x))lnIk+1=limx0[ln(fk(x)tanx)ln(gk(x)x]+fork=1byaboveproofwastrue+Supposeitistruen=1,2,...,kwhichmeansIk=limx0(lnfk(x)gk(x))=0k=1,2,...,kThenlnIk+1=lim[ln(fk(x)tanxgk(x)x)]=lim[tanxln(fk(x))xln(gk(x))]=limx0{tanx[ln(fk(x))ln(gk(x))]+tanxln(gk(x))}=0since[ln(fk(x))ln(gk(x))]=0byintroductionthehypothesisandln(xgk(x))0whenx0.Indeed,thiscanisprovebyinductionfollowsas:+fork=1wehavelimx0[xlng1(x)]==limx0(xlnx)=limx0lnx1x=limx01x1x2=limx0(x)=0+Supposeitistruen=1,2,...,kExtra \left or missing \right=0.0duetolim[ln(gk(x))]=0(byintroductionthehypothesis).Thisshowthatlimx0[xln(gk(x))]=0truen1Thus,weprovethatlnIk+1=0istrue,sobyintroductionprimciplelnIn=0istruen1.In=e0=1nN,n1(q.e.d)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com